Advances in inhaled corticosteroids for the treatment of chronic obstructive pulmonary disease: what is their value today?. (24th May 2022) - Cazzola, Mario; Ora, Josuel; Calzetta, Luigino; Rogliani, Paola; Matera, Maria Gabriella
ABSTRACT: Introduction: As of today, there is still a need to determine which COPD patients may benefit from ICS therapy, whether ICSs are useful in COPD patients without chronic bronchitis, and whether long-acting bronchodilators can reduce the risk of exacerbations in frequent exacerbators even if ICSs are not used, and whether combination therapy including ICSs is helpful in infrequent exacerbators to optimize the use of ICSs in COPD. Areas covered: Herein, the authors provide an overview of use of ICS in COPD, discuss their value to the current treatment armamentarium and focus on emerged aspects on which there is no consensus. Expert opinion: There is growing agreement on why, in whom, and when ICS therapy can be used in COPD, although the consensus is still lacking because of the heterogeneity of COPD. The use of BECs is only helpful in T2 inflammation, while there is a lack of biomarkers indicating the presence of T1 and T17 immunity, which is poorly responsive to ICS. Identifying ICS-sensitive endotypes using specific biomarkers that have yet to be identified and validated is likely to demonstrate that ICSs can influence the natural course of COPD in at least a subset of patients.